Quality of life and cost of illness in patients with psoriasis in Malaysia: a multicenter study. (17th February 2013) - Tang, Min Moon; Chang, Choong Chor; Chan, Lee Chin; Heng, Agnes
Abstract Background Psoriasis is an immune‐mediated, chronic, inflammatory skin disease which affects approximately 2% of the world's population. It has a major impact on the patient's quality of life (QoL), influencing career, social activities, family relationships, and all other aspects of life. Many studies have described the various ways in which psoriasis can affect a patient's life. Very little is known, however, about the impact of psoriasis on the QoL of patients treated in Malaysia and the cost of illness in this region. Objectives This study aims to describe the extent to which psoriasis affects the QoL of patients treated in government‐run dermatology clinics in Malaysia and to estimate the cost of illness. Methods A total of 250 psoriasis patients treated at eight dermatology clinics in government‐run hospitals in Malaysia were studied. The severity of psoriasis was assessed by dermatologists. Quality of life was evaluated using the Dermatology Life Quality Index (DLQI) and Version 2 of the 12‐Item Short‐Form Health Survey (SF‐12v2). Scores on the SF‐12v2 of healthy subjects and of patients with other medical conditions, such as depression, diabetes mellitus, hypertension, and ischemic heart disease, were also assessed for comparison. The costs of dermatology outpatient consultant fees, medications, investigations, procedures, transportation, over‐the‐counter medications, and hospitalization were retrospectively estimated using questionnaires. Results The cohort studied had a median Psoriasis Area Severity Index (PASI) score of 9.9 and a median DLQI score of 10.0. The average SF‐12v2 scores were 43.68 (standard deviation [SD] 9.23) and 42.25 (SD 10.7) on the Physical Health Summary and Mental Health Summary, respectively. The impact of disease on QoL was found to be greater in those with more extensive psoriatic lesion involvement, in younger patients, and in those with psoriatic arthropathy. Psoriasis was found to affect QoL in both genders equally. Body mass index had no effect on the severity of psoriasis or QoL. Patients with psoriasis had a significantly lower SF‐12v2 score than healthy subjects. Comparisons with data for patients with other chronic medical conditions demonstrated that psoriasis has a negative effect on health‐related QoL similar to the impact of other chronic conditions. The estimated cost of illness for psoriasis in the current cohort was ringgit Malaysia (RM) 1307.47 per person per year excluding costs of hospitalization. Patients were noted to spend a large amount of money on over‐the‐counter products obtained without doctors' prescriptions. Conclusions The QoL of patients with psoriasis was significantly impaired compared with that of healthy subjects and was comparable with that of patients with other chronic medical illnesses. The estimated cost of illness of psoriasis in the current study was lower than in other countries, mainly because healthcare costs in public hospitals are heavily subsidized by government and because usage of newer but more expensive treatment options is low in Malaysia.